Peran Pemerintah Dalam Pengelolaan Wisata Pasar Terapung Lok Baintan Di Desa Lok Baintan Kecamatan Sungai Tabuk Kabupaten Banjar - Rizki, Muhammad; Arbain, Taufik; Oktavianor, Tomi (Jurnal PubBis, 2025)
The management of river tourism, especially in the Lok Baintan Floating Market, is still less than optimal. This condition has resulted in a decrease in the number of traders and visitors, similar to what is currently happening in the Kuin Floating Market. In fact, tourism is an important sector that should be utilized for national development in order to improve people's welfare and income. This study aims to identify the government's response, role, and obstacles in managing the Lok Baintan Floating Market tourism. The method used is descriptive qualitative, namely by analyzing descriptive data in depth and linking it to relevant theories. This study involved 12 informants, consisting of representatives of the South Kalimantan Provincial Tourism Office and Banjar Regency, Pokdarwis Baintan Berseri, as well as traders and the surrounding community. Data were collected through observation, interviews, documentation, and audio and visual materials. This study highlights that the planning and arrangement of facilities at the Lok Baintan Floating Market have been successful with the concept of sustainable tourism. However, less intensive supervision because it only relies on community self-reliance is the main obstacle, which ultimately affects the number of traders and visitors. It is hoped that this study can be the basis for creating regulations that support a tourism-based creative economy in order to improve the competitiveness of destinations and people's welfare.  Keywords: Role; Management; Lok Baintan Floating Market Tour